تطبيقات القواعد والضّوابط الفقهيّة في أحكام الطّلاق عند المالكيّة - معتوق, الزبير (University of Eloued جامعة الوادي, 2021)
اقتضت طبيعة الموضوع تقسيمه إلى مقدمة، ومبحث تمهيدي، وبابين. أمّا المقدّمة فضمَّنتها الحديث عن أهمية الموضوع، وطرحٌ لإشكاليته، وسبب اختياره، وأهدافه، والدراسات السابقة له، والمنهج المتَّبع في إنجازه، والمنهجيَّة المسلوكة في كتابته، وحدوده، وخطَّته المرسومة لذلك، وأهمّ الصعوبات التي حاولت إعاقته. اشتمل المبحث التّمهيدي على ثلاثة مطالب؛ خُصِّص أوّلها للتعريف بالقواعد الفقهيّة وأهميتها والفروق بينها وبين المصطلحات ذات الصلة بها، وجُعل ثانيها لبيان ماهية الضّوابط الفقهيَّة والفروق بينها وبين القاعدة الفقهيَّة، وأمّا ثالثها فقد سلّط الضوء على الطّلاق، وذلك بتعريفه وبيان مشروعيته وحُكمِه وأركانِه وأقسامه. وجُعل الباب الأوّل للكلام عن القواعد الفقهيّة الكلّية الكبرى الـمُتعلِّقة بالطّلاق عند المالكيّة وما يندرج تحتها، فجاء في خمسة فصول، وأمّا الباب الثّاني فاحْتوى فصلين، خُصِّص الأوّل لبيان القواعد الفقهيّة الكُلِّيَّة الصُّغرى المتعلِّقة بالطّلاق عند المالكيّة، فجاء في أربعة مباحث، وعُنِي الثّاني بالضّوابط الفقهيّة المتعلِّقة بالطّلاق عند المالكيّة فجاء في خمسة مباحث. وكانت الخطّة التي اتّبعتُها أنْ أَذكُر القاعدة الرّئيسة، ثُمّ الصِّيغ المتعلِّقة بها، وأَشرحُ معنى القاعدة وصِيغها المختلفة، ثُمَّ أقوم بالتّأصيل لها مع بيان تطبيقاتها الفقهيّة واستثناءاتها إن وُجدت. وأقوم بالشّيء نفسه مع الضّوابط الفقهيّة. وقد بلغ مجموع القواعد الفقهيّة في الأطروحة ثمانية وخمسين قاعدة، ومجموع الضّوابط الفقهيّة سبعة عشر ضابطًا. ومن أهمِّ الّنتائج التي خُتم بها البحث أنّ للمذهب المالكي دوره البارز في تأصيل القواعد والضوابط الفقهيّتين وتقْعيدهما، وأنّ الملاحظ على القواعد والضّوابط الفقهيّة المدروسة كثرة صِيغها، مع تأدِيَتِها -في الأعمّ الغالب- معنى واحدًا، وأنّ القواعد الفقهية عندهم تميّزت بالإشارة إلى الخِلاف من خلال صياغتها الاستفهاميّة، وأنّ عددًا لا بأس به من التطبيقات انفردوا بها عن غيرهم، وأنّ للعُرف وللاحتياط دورٌ كبيرٌ في صياغة القواعد والضّوابط الفقهيّة لديهم في كثير من مسائل الطّلاق، وخاصة ما تعلّق منها بالألفاظ. كما ظَهر من خلال التطبيقات التي بُحثت أنّ أوْسع المذاهب قولًا في باب الطلاق هم المالكية، إذ لو أخذنا بقولهم لاتّسعت دائرة الطّلاق بدل تضييقها؛ ومن أسباب ذلك توسّعهم في الأخذ بالعُرف والاحتياط وخاصّة ما تعلّق بالفروج، وعلى ضوء هذا أَوْصى البحث بأن تُراعى في الفتوى والقضاء المتعلّقة بأحكام الطّلاق المصلحة واعتبار المآل، ولو أدّى ذلك إلى الخُروج عن مشهور المذهب المالكي. The Nature of the subject required from me to devide it to an introduction, front matter, and two main units. The introduction outlined the importance of the topic, Bringing up the topic problematic, the reason for its choice, its objectives, previous related studies, the methodology, the limits, and the plan drawn for that, and the most important difficulties that I tried to hinder him. The front matter is devided into three demands, the first was devoted to defining the jurisprudence, its importance and its differences with the relevant terminology, the second state the nature of the juriprudencial controllers and the differences between them and the jurisprudence rules and the third highlight divorce by defining it and stating its legitimacy, judgment, pillars and sections. The first unit objective is to talk about the Major jurisprudential rules concerning divorce at the Malikis and what falls under them, this unit was divided into five chapters; the second unit was devided into two chapters, The first was devoted to a statement of the Non-Normative Legal Maxims related to divorce at the Malikis, and it comes in four themes, and the second chapter was concerned about the jurisprudential regulations related to divorce at Malikis and it came in five themes.The plan i followed was to state the basic rule, then the formulas related to it, explain the meaning of the rule and its various formulas, and then rooting jurisprudencial applications and its exceptions if exist, its implications, and I do the same with doctrinal regulations. The total number of djurisprudence rules in the thesis was fifty-eight, and the total of jurisprudencial controllers are seventeen. One of the most important results concluded by the research is that the Maliki doctrine has a prominent role in rooting the rules and controllers of jurisprudence and their status. It is noticed that the studied rules and controllers of jurisprudence are many in their formulas, while performing -in the most general sense- one meaning, and their jurisprudential rules were distinguished by referring to the dispute through their interrogative worded, and a good number of applications were unique to them, custom and precaution have a great role In drafting the jurisprudential rules and controllers they have in many matters of divorce, especially those related to expressions. As it appeared through the applications the Malikis doctrine is the broadest doctrines in terms of divorce, if we adopt their view the divorce cycle would have widened rather than narrowed, One of the reasons for this, is their expansion in the adoption of custom and precaution, especially with regard to pudenda, in light of this the research recommended that the fatwa and the judiciary related to the ruling of divorce be taken into consideration the benefit and consideration of the outcome, even if that leads to to derogate from the popular view of Maliki school
أطروحة دكتوراه في العلوم الإسلامية تخصص فقه وأصول
Keywords: القواعد الفقهية، الضوابط الفقهية، الطلاق، المالكية; Jurisprudence rules, jurisprudential controls, divorce, Maliki